THE EFFECT OF SUPPLIER RELATIONSHIP MANAGEMENT ON THE SUCCESS OF FOOD AND BEVERAGE PRODUCERS IN KENYA - Kariuki, Fiona M.; Kitavi , Samuel N. (Ayden International Journal of Banking, Finance and Technology, 2024)
Effective supplier relationship management (SRM) has been identified as a critical factor for improving the performance of firms in the supply chain. Poor relationship management can lead to high acquisition costs, long lead times, lower quality materials, poor reputation, low sales, low market share, and low profitability. This study investigates the influence of SRM on the performance of food and beverage manufacturing firms in Kenya. Specifically, the study examines the impact of supplier segmentation, supplier collaboration, information flow, and supplier development on organizational performance. A crosssectional survey design was used, incorporating both qualitative and quantitative approaches. The target population consisted of officers working in procurement, warehousing, and logistics departments in 63 food and beverage organizations in Kiambu County. A total of 189 officers were sampled using census and purposive sampling techniques, and data was collected through questionnaires. The study found that supplier segmentation, information flow, supplier collaboration, and supplier development have a positive influence on the performance of food and beverage manufacturing firms in Kiambu County. Correlation analysis showed that these factors were positively and significantly correlated with organizational performance. The study also found that management in the food and beverage sector in Kiambu County embraces these elements of SRM.The study concludes that developing effective strategies for managing supplier relationships can significantly improve the performance of food and beverage manufacturing firms. This study's findings have practical implications for managers in the sector, highlighting the importance of effective supplier relationship management in achieving a competitive edge.